Maker projects for kids who love robotics - Bow, James (Be a maker!, 2016)
"In this exciting title, readers will learn about basic robot components and how they are used to build various robots for different purposes. "Makers and Shakers" sidebars introduce the world's greatest robot designers and explain how they came to create their exciting inventions. Step-by-step Maker projects let readers put their skills to use as they build amazing robotic creations."--